Smart Dialogue for Smart Citizens: Assertive Approaches for Strategic Planning - Fasolino, Isidoro; Izzo, Maria Veronica (TeMA - Journal of Land Use, Mobility and Environment, 2014)
It is very important to know how to communicate, but even more important is knowing how to listen. There is no dialogue without listening. Listening and speaking can generate a virtuous cycle that, enriching the field of information, allows the introduction of essential elements of innovation. It is relevant in this context the assertive ability of who manages and coordinates the decision-making processes. The potential of new approaches based on assertiveness are the new frontier of research discipline that is able to meet future challenges aiming to contribute to the construction of places and forms of living together in the growing interest of fairness and justice. Assertive facilitator knows how to guide difficult people and handle very hard situations without adopting manipulative behaviors. He is able to detect the potential conflict and to bring to light the reasons for disagreement , softening the tone and avoiding any possible uncontrolled escalation. He encourages debates and open discussions; he has to build links too, fueling reports profits, collaborating with others toward common goals; speaking and discussing in groups and among groups; seeking solutions in which, both parties, come out winning. So the view expressed is argument of discussion in the development of the tools of urban structure, with the aim of implementing a participatory methodology in the development of planning tools. We propose an application in the series of meetings of initial preparatory participation to the formation of a Preliminary Plan for a medium size town.